Ectopic Solitary Cortical Anaplastic Ependymoma in a Child: A Rare Entity with Short Illustrative Review - Guthe, Sachin; Survashe, Pravin; Velho, Vernon; Bhopale, Laxmikant; Darade, Poonam (Indian Journal of Neurosurgery, 2018)
Ependymomas are usually infratentorial and intraventricular. They originate from the ependymal cell lining of the ventricles. Cortical extraventricular supratentorial ependymomas are rare and fewer than 15 cases are reported worldwide. In pediatric age group, seven cases are reported. We report a rare case of 4-year-old boy with right frontoparietal anaplastic ependymoma who underwent gross total excision of lesion.
Keywords: anaplastic; cortical; pediatric ependymoma